Environmental regulation, industrial transformation, and green economy development - Shao, Huimin; Peng, Qiong; Zhou, Fei; Wider, Walton (Frontiers in Environmental Science, 2024)
Green development, which is crucial because of the escalating ecological and environmental issues, is largely driven by industrial transformation and environmental legislation. The paper examines the combined effects of environmental regulations and industrial change on the green economy, based on their separate effects. We reach the following conclusions from a fixed-effects regression on panel data covering 30 provinces in China in 2010–2020: environmental regulations and rationalization of the industrial structure both support growth in the green economy, but advancement in the industrial structure hinders it. The combined effect of environmental regulations and advancement and rationalization in the industrial structure has a significantly positive impact on growth in the green economy; it is most pronounced in regions with higher resource endowments and economic development. By providing specific empirical facts, this study clarifies the effects of industrial transformation and environmental regulations on growth in the green economy, contributing to enriching the literature and helping to pave the way to sustainable development.